Indications for haematopoietic stem cell transplantation for haematological diseases, solid tumours and immune disorders: current practice in Europe, 2019 - Duarte, Rafael F.; Dreger, Peter (Bone marrow transplantation, 2019)
This is the seventh special EBMT report on the indications for haematopoietic stem cell transplantation for haematological diseases, solid tumours and immune disorders. Our aim is to provide general guidance on transplant indications according to prevailing clinical practice in EBMT countries and centres. In order to inform patient decisions, these recommendations must be considered together with the risk of the disease, the risk of the transplant procedure and the results of non-transplant strategies. In over two decades since the first report, the EBMT indications manuscripts have incorporated changes in transplant practice coming from scientific and technical developments in the field. In this same period, the establishment of JACIE accreditation has promoted high quality and led to improved outcomes of patient and donor care and laboratory performance in transplantation and cellular therapy. An updated report with operating definitions, revised indications and an additional set of data with overall survival at 1 year and non-relapse mortality at day 100 after transplant in the commonest standard-of-care indications is presented. Additional efforts are currently underway to enable EBMT member centres to benchmark their risk-adapted outcomes as part of the Registry upgrade Project 2020 against national and/or international outcome data.
Gesehen am 29.10.2019